Anti-inflammatory Effects of the Stem Barks from Albizia Ferruginea (Mimosaceae) on Chronic Inflammation Induced in Rats - Martin Thierry, Bella Ndzana; Minoué Kuum, Marc Germain; Temdie Guemmogne, Roméo Joël; Tchadji, Jules Colince; Lissom, Abel; Dimo, Théophile (International Journal of Innovative Research in Medical Science, 2018)
Albizia ferruginea is used in popular medicine for the treatment of inflammatory illnesses. The chronic anti-inflammatory effects of aqueous extract of A. ferruginea was assessed on the cotton pellet-induced granuloma, formalin and complete Freund's adjuvant-induced inflammation. The aqueous extract of A. ferruginea was administered orally at the doses of 100 and 200 mg/kg. It’s showed that A. ferruginea extract (100 or 200 mg/kg) significantly (p<0.001) inhibited the granuloma formation induced by cotton pellets by 41.70 % and 46.10 %, respectively. A. ferruginea extract, at the dose of 200 mg/kg inhibited (p<0.01) the paw œdema induced by formalin (25.79 %) and Complete Freund’s adjuvant (CFA) in rats(47.40 %).A. ferruginea extract(100 or 200 mg/kg) normalized the level of white blood cells, red blood cells, hemoglobin, and platelets of rats treated with CFA. Glutathione and superoxide dismutase levels were significantly increase (92.59% and 60.51%, respectively), catalase activity was significantly increased (42.03%) in the tissue of CFA rats treated with A. ferruginea (200 mg/kg). Malondialdehyde level was reduced by 72.88% (p<0.01) in spleen of rats treated with A. ferruginea aqueous extract. The nitrite level was significantly decreased by 50.51% in liver of CFA rats treated with A. ferruginea (200 mg/kg). These results show that aqueous extract of A. ferruginea may possess anti-inflammatory effects on chronic inflammation, which could be partially attributed to its antioxidant properties.